Explant Sterilization and Shoot Induction Techniques in Micropropagation of Tembesu (Fagraea fragrans Roxb.) TEKNIK STERILISASI EKSPLAN DAN INDUKSI TUNAS DALAM MIKROPROPAGASI TEMBESU (Fagraea fragrans ROXB) - Rhomi Ardiansyah; Supriyanto .; Arum Sekar Wulandari; Benny Subandy; Yuli Fitriani (Jurnal Silvikultur Tropika, 2014)
Tembesu (Fragraea fragans Roxb) is important tree species for furniture due to its decorative structure, but its propagation facing to the problems on seed availability. Determining explant sterilization technique of tembesu (Fagraea fragrans Roxb.) in in vitro condition is needed to produce aseptic explants for shoot induction in micropropagation techniques. Shoot induction of explants depends on plant growth regulator and growth medium compositions. This study was aimed (1)to analyzing the effect of sodium hypochlorite 10% in sterilization process to obtain aseptic explants, (2) to find out plant growth regulator and growth medium composition on shoot induction of tembesu (F. fragrans Roxb.) in in vitro condition. This study was conducted at Tissue Culture Laboratory, Rumpin Seed Source and Nursery Center, The Ministry of Forestry, Bogor on February – June 2014. Explants were sterilized using sodium hypochlorite (NaOCl 5.25%) at 10% of concentrations in various durations (5, 10, 15, and 20 minutes). Shoot induction was done using MS medium, MS modified medium, and MS added with 15% coconut water that combined with 1.5 ppm of BAP. The result showed that explants soaked in sodium hypochlorite 10% within 20 minutes was recommended for explants steriliziton technique of tembesu. Combination treatment between BAP 1.5 ppm and MS modified medium was the most favorable culture medium for shoot induction of tembesu.Keyword: Benzylaminopurine, Fagraea fragrans, micropropagation, Murashige-Skoog modified, sodium hypochlorite